â€œPEPRADASEâ€ PELATIHAN PRAKTIKUM BIOLOGI DENGAN ALAT DAN BAHAN SEDERHANA - Lubis, Fitri Agustina; Lubis, Jalilah Azizah; Lubis, Mutiara (Universitas Muhammadiyah Tapanuli Selatan, 2017)
Objectives of the Activity This training is expected to be more creative in teaching practicum and teaching planning by applying the right strategy to develop teachers' creativity in using simple tools and materials when practicum and student interest to learn more in improving scholarship in biology learning. This devotion is done in SMA Negeri 5 Kota Padangsidimpuan, the time of implementation is adjusted to the MGMP Teacher - High School Biology subject. This dedication is executed for two months from January - February 2017 where the activities are done for four days in thedifferentperiod.The result of this teaching materials development workshop is that the teachers of Biology at SMA Kota Padangsidimpuan have gained much motivation, related information / knowledge in developing lesson plan and making of practicum with simple materials also predicted in the future the teachers of Biology especially in SMA are able develop simple practice materials on their own.Keywords: Training, Development of RPP, Simple Practicum.